2001
DOI: 10.1007/s004420000616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seedling size, El Niño drought, seedling density, and distance to nearest conspecific adult on 6-year survival of Ocotea whitei seedlings in Panamá

Abstract: We present an analysis of the long-term survival of two cohorts of seedlings of the tropical canopy tree Ocotea whitei (Lauraceae) on a 1-ha plot of mature, lowland moist forest on Barro Colorado Island, Panamá. In 1980, we counted an even-aged cohort of seedlings that germinated in 1979, then measured and tagged survivors in 1981. We also measured and tagged a second, smaller cohort of seedlings that germinated in 1981. We followed the subsequent survival of all seedlings through 1985. Seedling mortality was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 42 publications
8
99
1
4
Order By: Relevance
“…Both pathogens and insects have been shown to cause densitydependent mortality in established seedlings and saplings (Wong et al 1990, Gilbert et al 2001. Negative effects of conspecific neighbors may also result from intense competition between conspecifics.…”
Section: Effect Of Conspecific Neighbors On Established Seedling Survmentioning
confidence: 99%
“…Both pathogens and insects have been shown to cause densitydependent mortality in established seedlings and saplings (Wong et al 1990, Gilbert et al 2001. Negative effects of conspecific neighbors may also result from intense competition between conspecifics.…”
Section: Effect Of Conspecific Neighbors On Established Seedling Survmentioning
confidence: 99%
“…In a wider analysis of 60 species using the same size class and a nearest neighborhood modeling approach, Uriarte et al (2004b) found only weak evidence of conspecific effects for six species: they suggested that once a tree at BCI moved from seedling to sapling or pole sizes, NDD was lost (Uriarte et al 2005). Gilbert et al (2001) showed a pathogen-specific small-tree effect for one particular species at BCI. Interestingly, we are not aware of any literature reporting main tests of NDD on growth of trees !4 cm dbh at BCI.…”
Section: Introductionmentioning
confidence: 99%
“…La heterogeneidad en la estructura de tamaño en las plántulas de E. uribei es una situación común dentro de las poblaciones vegetales y se asocia a diferencias en el acervo genético de los individuos, el tiempo de germinación, las tasas de crecimiento, interacciones de competencia, de facilitación (Hutchings, 1997;Silvertown y Charlesworth, 2001;Lopera, 2010), efectos denso-dependientes, depredación por herbívoros, el ataque de patógenos, la caída de ramas o la falta de recursos suficientes para el crecimiento (Gilbert et al, 2001).…”
Section: Familia Especie Cobertura Relativa (%) Micrositiounclassified